Effects of Ashwagandha Supplements on Cortisol, Stress, and Anxiety Levels in Adults: A Systematic Review and Meta-Analysis - George Bachour; Abdullah Samir; Saddik Haddad; Mohamed Amine Houssaini; Menatallah El Radad (BJPsych Open)
Aims: Withania somnifera widely known as “Ashwagandha”, is a key treatment herb in the Indian system of medicine that has been used for thousands of years. It has anti-inflammatory, neuroprotective, adaptogenic, and immunomodulatory activities.